Corporate Governance dan Audit Delay (Penelitian Beberapa Skripsi dan Jurnal, Meta Analisis) - Athalia Elsha Pinontoan; Marisha Gabrila Sutanto; Michelle Lesmana; Carmel Meiden (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
The topic of the influence of corporate governance on audit delay has been studied by many researchers and still exists today. Existing studies show consistent and discordant findings with varying degrees of importance. This study attempts to synthesize the findings of university thesis and journals on corporate governance issues and their effect on audit delay in Indonesia from 2009 to 2019. The data collection method is observation with thesis output. The sample size for this study is 23 and consisting of student theses and journals. The sampling technique used is purposive sampling. The researcher uses meta-analysis techniques to synthesize the findings from the thesis and draw conclusions about the effect of corporate governance on audit delay. Profitability, the board of commissioners, independent commissioners, and the audit committee all have an effect on audit delay, according to the findings of this study. The independent variable has a weak correlation with the dependent variable, as indicated by the mean correlation value of less than 0.25. In addition, this study establishes the validity of agency theory in various manufacturing, banking, and LQ45 companies from 2009 to 2019. Keywords: audit delay; corporate governance; meta analysis